2015
DOI: 10.1007/s11010-015-2496-x
|View full text |Cite
|
Sign up to set email alerts
|

Derlin-1 is overexpressed in human colon cancer and promotes cancer cell proliferation

Abstract: Derlin-1 is overexpressed in many types of solid tumors and plays an important role in cancer progression. However, the expression pattern and functions of Derlin-1 in human colon cancer are not fully understood. In the present study, we examined Derlin-1 expression in colon cancer cell lines and human tissues and investigated its role in colon cancer. We found that Derlin-1 expression was increased significantly in colon cancer tissues and its overexpression correlated with the tumor differentiation, Dukes st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 24 publications
4
34
1
Order By: Relevance
“…These data demonstrate that the levels of Derlin-1 protein expression were elevated in the majority of BC tissues compared with normal bladder tissues. Our results are consistent with those of previous studies showing that Derlin-1 is overexpressed in various types of human cancers [1315, 27]. …”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…These data demonstrate that the levels of Derlin-1 protein expression were elevated in the majority of BC tissues compared with normal bladder tissues. Our results are consistent with those of previous studies showing that Derlin-1 is overexpressed in various types of human cancers [1315, 27]. …”
Section: Discussionsupporting
confidence: 94%
“…Almost all solid tumors growth depends on an intact unfolded protein response and tolerance of ER stress, such as hypoxia [2426]. In human breast, lung, and colon cancer, several lines of direct evidence demonstrated a significant association between Derlin-1 up-regulation and tumor grade, as well as between Derlin-1 up-regulation and lymph node metastasis [14, 15, 27]. …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, experiments of double-transfection by upregulating DERL1 in miR-181d-overexpressed ESCC cells revealed that DERL1 reversed the tumor suppression of miR-181d overexpression on ESCC proliferation, migration and cell cycle transition. DERL1 was often found to be overexpressed in human cancers, including colon (15), lung (17) or pancreatic cancer (16). Thus, our data are in line with previous studies, showing that DERL1 could be an active oncogenic gene in various types of human cancers, including ESCC.…”
Section: Discussionsupporting
confidence: 92%
“…In human cancers, DERL1 has been mostly reported to be an oncogene of regulating carcinoma progression. In colon cancer, DERL1 was upregulated in carcinoma tissues and promoted cancer proliferation (15).…”
Section: Introductionmentioning
confidence: 99%
“…We identified DERL1 as a direct downstream target gene of miR-598 using bioinformatics method that was further confirmed by the luciferase reporter assay. DERL1 is overexpressed in NSCLC; it also promotes cancer cell invasion via EGFR-ERK-mediated upregulation of MMP-2 and MMP-9 [16, 19, 21]. However, the correlation between DERL1 and miR-598 remains unclear.…”
Section: Discussionmentioning
confidence: 99%